Temporary Detention in Investigating Criminal Cases and Their Legal Consequences - Akli, Zul; Abidin, Zainal; Nasir, Muhammad; Johari, Johari; Zulkifli, Zulkifli (Interdisciplinary Social Studies, 2021)
Background: In the provisions of Article 28(A) of the 1945 Constitution it is stated that "everyone has the right to live and has the right to maintain his life and life. "This guarantee is not only limited to the order of discourse, the realization of the guarantee can be seen in the Criminal Code and in the provisions of Law No. 8 of 1981 concerning the Criminal Procedure Law (KUHAP) also aims to find and obtain material truth or at least approach the complete material truth. Aim: To uphold the rule of law, thus realizing a national legal system that serves the national interest based on justice and truth. Method: This research is normative legal research, so it requires primary legal material sourced from primary sources, namely legislation, official records or treatises in the making of legislation, and judge's rulings related to the formulation of the problem Findings: The temporary detention in the examination of criminal cases based on the provisions of Article 21 of the Kuhap is appropriately carried out by the relevant parties, but there are still many weaknesses faced. Although the purpose of temporary detention is to detain criminals temporarily, for learning and law enforcement in the community, to realize legal certainty in the midst of society, detention is also only the result of a choice over the purpose of law enforcement that is temporarily taken.